IoT based Monitoring System for Drought Prediction - Nafeela Banu, N; Deepika, G (International Journal of Computer Sciences and Engineering, 2025)
Drought is arguably the single biggest threat climate change. Its impacts are global. Therefore, there is a need for technological intervention to monitor basic information about the weather and soil condition, in order to identify and predict drought. The proposed wireless sensor drought monitoring system is capable of remote real-time monitoring for extended periods, identifying drought in the early stages. A combination of wireless sensor networks using TEEN (Threshold sensitive Energy Efficient sensor Network protocol) along with cloud technology would make data on humidity and salinity of the soil, temperature and light intensity on the surface that are accessible to end users. The data collected would then be transmitted to a public or hybrid cloud through satellite transmission protocols. Mobile cloud computing apps can be developed to raise an alarm when the drought conditions approach the critical stage. In this paper, we propose a novel IoT based monitoring system that assimilates data from real time weather and soil condition sensors. Thus providing a mobile client with which the user can monitor the drought conditions throughout the country, thereby indicating promptly when to take corrective measures.